Virtue Ethics and Integration in Evidence-Based Practice in Psychology - Berg, Henrik (Frontiers in Psychology, 2020)
The policy statement for evidence-based practice in psychology is the most important document in contemporary psychotherapy. In its current form, evidence-based practice in psychology gives scientific research precedence in psychotherapy practice. However, psychotherapy practice’s complexity warrants reflection beyond the limits of science. The importance of clinical expert is not recognised in the current policy statement. The clinical expert is necessary to translate psychological research into clinical practice. It is also crucial to identify, clarify and include patient preferences in psychotherapy practice. This paper argues that virtue ethics is a useful theoretical framework for conceptualising clinical expertise. Clinical expertise is conceptualised as the meta-capacity of practical wisdom (phronesis) and the virtues necessary for integrating best available research, clinical expertise and patient preferences.